2012
DOI: 10.1371/journal.ppat.1002776
|View full text |Cite|
|
Sign up to set email alerts
|

Multilocus Sequence Typing as a Replacement for Serotyping in Salmonella enterica

Abstract: Salmonella enterica subspecies enterica is traditionally subdivided into serovars by serological and nutritional characteristics. We used Multilocus Sequence Typing (MLST) to assign 4,257 isolates from 554 serovars to 1092 sequence types (STs). The majority of the isolates and many STs were grouped into 138 genetically closely related clusters called eBurstGroups (eBGs). Many eBGs correspond to a serovar, for example most Typhimurium are in eBG1 and most Enteritidis are in eBG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
652
4
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 590 publications
(702 citation statements)
references
References 95 publications
27
652
4
19
Order By: Relevance
“…The phylogeny of these serotypes is largely consistent with previous studies showing that S. Dublin represents an independent clade (9,11). Our data show that there are ∼23,000 SNPs differentiating S. Dublin from the most recent common ancestor of S. Enteritidis and the avian-adapted salmonellae, S. Gallinarum and S. Pullorum.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The phylogeny of these serotypes is largely consistent with previous studies showing that S. Dublin represents an independent clade (9,11). Our data show that there are ∼23,000 SNPs differentiating S. Dublin from the most recent common ancestor of S. Enteritidis and the avian-adapted salmonellae, S. Gallinarum and S. Pullorum.…”
Section: Resultssupporting
confidence: 90%
“…Somatic serogrouping and MLST have identified a single lineage with closely related members that exhibit a range of different host specializations (6)(7)(8)(9). These include two of the most important Salmonella pathogens: S. Enteritidis and S. Gallinarum.…”
Section: Significancementioning
confidence: 99%
“…Owing to the slow mutation rate of housekeeping genes, MLST often does not display the resolution of PFGE or MLVA, but is the method of choice for long-term epidemiological and phylogenetic investigations. In our laboratory, MLST was used for typing of particular S. enterica serovars (Zeinzinger et al, 2012) and we were able to confirm that MLST has the discriminatory power to type isolates beneath serotype level (Achtman et al, 2012;Zeinzinger et al, 2012).…”
Section: Multi-locus Sequence Typing (Mlst)supporting
confidence: 57%
“…A methodical exception to the shift from conventional to molecular typing techniques is the classical serotyping of S. enterica. Although it has been shown that many Salmonella serotypes comprise strains that have completely different genotypes because of lateral gene transfer of flagella genes (Achtman et al, 2012), implementation of suitable molecular methods is still an issue. Several molecular methods such as PFGE, MLVA, MLST, and HRM have been proposed as alternatives for serotyping but all are hindered by the fact that a one-to-one comparability between serotyping and molecular typing results is impossible.…”
Section: Resultsmentioning
confidence: 99%
“…enterica subtyping by Wattiau et al emphasizes the importance of DNA-based typing schemes (44). Furthermore, the latest MLST findings can demonstrate evolutional grouping better than serotyping, which sometimes can mislead an epidemiological investigation (45).…”
Section: Discussionmentioning
confidence: 99%